2019
DOI: 10.1155/2019/1472487
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Food Choice among Pastoral/Agro-Pastoral Community in Somali Regional State, Eastern Ethiopia

Abstract: Background. Although nutritional problems are among the Ethiopian government’s priorities, the progress of nutritional indicators in the pastoral/agro-pastoral community is below the national figure. This could be because of poor food choice decisions, which remains poorly understood. Therefore, this study aimed to explore the drivers of food choice among the pastoral/agro-pastoral community of Somali Regional State, Eastern Ethiopia. Materials and Methods. A qualitative study was conducted among 16 Focused Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…This study indicated that price, convenience, availability, household preference, household food production, food quality, and advertisement are important drivers of food choice. This is similar with other studies ndings in Ethiopia (38)(39)(40). Food choice factors are variable across populations and regions due to cultural diversity and socio-economic differences (29,30,36).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study indicated that price, convenience, availability, household preference, household food production, food quality, and advertisement are important drivers of food choice. This is similar with other studies ndings in Ethiopia (38)(39)(40). Food choice factors are variable across populations and regions due to cultural diversity and socio-economic differences (29,30,36).…”
Section: Discussionsupporting
confidence: 92%
“…The present study also showed the importance of availability of a wide variety of healthy and safe foods in food choice. This nding is similar with previous studies in Addis Ababa (39) and among pastoralists in Ethiopia (40). In New Zealand, some consumers prefer locally available foods and are unwilling to purchase non-locally produced food at any price (51).…”
Section: Discussionsupporting
confidence: 91%
“…A study conducted in Ethiopia's Somali Region revealed that residents have monotonous feeding habits and poor food choices, with food choice drivers such as crop failure, income, price, quality and availability of foods, market access, familiarity with new foods, knowledge of nutritious foods, and individuals' health status being mentioned. 23 Similarly, the recent study found that price and familiarity were remained the most important motivators. The previous research, however, did not report on mood or health concerns.…”
Section: Discussionmentioning
confidence: 90%
“…A previous study also demonstrated inadequate access to safe drinking water in these regions [48], which may in turn increase the burden of intestinal parasites, diarrhoeal diseases, and undernutrition. The highest inequality in access to minimum nutrition was found in the Somali and Afar regions, primarily because a majority of their food items are imported from other areas [49]. Inaccessibility of transportation further jeopardises the availability of imported nutritious foods.…”
Section: Discussionmentioning
confidence: 99%